What is the clinical impact of occult HBV infections and anti‐HBc positivity in patients with chronic hepatitis C?. (29th June 2022) - Cakal, Bulent; Cavus, Bilger; Atasoy, Alp; Poda, Mehves; Bulakci, Mesut; Gulluoglu, Mine; Demirci, Mehmet; Sener, Leyla Turker; Altunok, Damla; Arslan, Asli Berru; Akyuz, Filiz
Abstract: Occult hepatitis B infection (OBI) is defined by the persistence of the hepatitis B virus (HBV) genome in the liver of individuals testing negative for hepatitis B surface antigen (HBsAg). Hepatitis B core antibody (anti‐HBc) is the serological marker that indicates HBV exposure. The impact of anti‐HBc and OBI on patients with chronic hepatitis C remains unclear. The aim of the present study was to determine the prevalence of anti‐HBc and OBI and to evaluate their impact on the clinical and pathological outcomes of patients with chronic hepatitis C. The study included 59 HBsAg‐negative chronic hepatitis C patients who underwent a liver parenchymal biopsy. The presence of HBV DNA was investigated using an in‐house nested PCR method. OBI was detected in 16 (27.1%) of the 59 cases and also in 10 (62.5%) of 22 (37.3%) anti‐HBc‐positive patients. None of the patients had positive serum HBV DNA. OBI was associated with the presence of anti‐HBV antibodies ( P  < 0.05). There was also an association between anti‐HBc positivity and the activity grades and fibrosis stages of the liver and also a prevalence of liver steatosis ( P  < 0.05). Positive anti‐HBc results may predict OBI and may also be associated with the progression of liver injury in HBsAg‐negative patients with chronic hepatitis C. Therefore, it is suggested that patients with chronic hepatitis C should be screened for anti‐HBc positivity, and anti‐HBc‐positive patients should be carefully evaluated for disease progression.